Evolving Management of Symptomatic Chronic Subdural Hematoma: Experience of a Single Institution and Review of the Literature - Balser, David (Neurol Res, 2013)
OBJECTIVE: Chronic subdural hematoma has an increasing incidence and results in high morbidity and mortality. We review here the ten-year experience of a single institution and the literature regarding the treatment and major associations of chronic subdural hematoma (cSDH). METHODS: We retrospectively reviewed all cSDHs surgically treated from 2000 to 2010 at our institution to evaluate duration from admission to treatment, type of treatment, length of stay in critical care, length of stay in the hospital and recurrence. The literature was reviewed with regards to incidence, associations and treatment of cSDH. RESULTS: From 2000–2008, 44 patients were treated with burr holes. From 2008 to 2010, 29 patients were treated with twist drill evacuation (SEPS). 4 patients from each group were readmitted for reoperation (9% vs. 14%; p=.53). The average time to intervention for SEPS (11.2±15.3 hrs) was faster than for burr holes (40.3±69.1 hrs) (p=.02). The total hospital LOS was shorter for SEPS (9.3±6.8 days) versus burr holes (13.4±10.2 days) (p=.04); both were significantly longer than for a brain tumor patient undergoing craniotomy (7.0±0.5 days, n=94, P<.01). CONCLUSION: Despite decreasing lengths of stay over time as treatment for cSDH evolved from burr holes to SEPS, the length of stay for a cSDH is still greater than that of a patient undergoing craniotomy for brain tumor. We noted 11% recurrence in our series of patients, which included individuals who recurred as late as 3 years after initial diagnosis.